A Systematic Review of Learning Theory on Computational Thinking - Wan Nor Ashiqin Wan Ali; Wan Ahmad Jaafar Wan Yahaya, (Journal of Human Development and Communication (JoHDeC), 2025)
This paper reviews systematically theory used in the past studies on computational thinking, learning theory used in past studies on computational thinking and explore how these learning theories on computational thinking can be improved for future studies conducted in Malaysia. Today, computational thinking is not just an ability that only focuses on computer scientist and being adapted by them, but an ability for everyone needs. It is because computational thinking is changing the way we think and become an integral part of our daily life. 18 out of 126 articles were identified for analytical purposes in tandem with the observed theme under keywords searched “theory AND computational thinking, theory on computational thinking” and 2 out of 4 articles were identified under keywords searched “learning theory AND computational thinking, learning theory on computational thinking”. This paper aims to study what are the recognised learning theory being studied and focused on computational thinking scope research areas. Further exploration on the type of research theory, type of intervention and respondent as well as technology being used or developed are discussed in details in this paper. The study findings highlight that constructivist learning theory is the well-known learning theory being used in computational thinking research area which focuses on primary and secondary school students in worldwide.